APLlKASl SlSTEM KEUANGAN DESA (SlSKEUDES) VERSl 2.0.3 DALAM MENlNGKATKAN KUALlTAS AKUNTABlLlTAS KEUANGAN DESA PADA MASA PANDEMl COVlD-19 DI KABUPATEN TULUNGAGUNG - Amelisa, Elsanda; Susilowati, Lantip (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2022)
This research intends to understand the application of the Village Financial System (SlSKEUDES) version 2.0.3 to the quality of village financial accountability during the COVID-19 pandemic in Tulungagung Regency and to understand its impact on the quality of accountability and develop operational efficiency. Qualitative research method is used in this research. The data used are primary data and secondary data obtained from observations and interviews. The analytical methods used are data collection, data reduction, data presentation and drawing conclusions. The results of the research show that the implementation of the SlSKEUDES version 2.0 application is in accordance with the procedure. After the implementation of the SlSKEUDES application version 2. 0. 3, the quality of village financial accountability has increased and the creation of clear and accountable financial reports. As a result, the performance of using the SlSKEUDES application version 2. 0. 3 is rated more positively. such as simplifying village financial reports, shortening time, while the constraints experienced are network limitations and system errors in using the SISKEUDES application version 2.0.3.